2015
DOI: 10.1136/archdischild-2015-308306
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of school teachers, preschool teachers and students in teacher training about epilepsy and emergency management of seizures

Abstract: Training programmes for teachers should be established. Furthermore, a clear legal regulatory framework needs to be set up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 36 publications
7
28
1
2
Order By: Relevance
“…Earlier studies have also demonstrated that teachers are not adequately trained and prepared to manage emergencies dealing with long‐term illnesses . These facts seem to result in fear of litigation should something untoward occur …”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Earlier studies have also demonstrated that teachers are not adequately trained and prepared to manage emergencies dealing with long‐term illnesses . These facts seem to result in fear of litigation should something untoward occur …”
Section: Discussionsupporting
confidence: 86%
“…Accordingly, it seems that teachers have to rely on their personal experience of medicating long‐term illnesses in their own children in order to administer medicines at school. Previous studies have demonstrated that teachers have concerns related to inexperience and lack of knowledge about long‐term illnesses . Earlier studies have also demonstrated that teachers are not adequately trained and prepared to manage emergencies dealing with long‐term illnesses .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, lorazepam is a viscous substance with only a few studies of nasal administration. 40 A wide availability of socially nonembarrassing and inexpensive alternatives to rectal diazepam together with educational campaigns may change these perceptions and help optimize the pre-hospital treatment of prolonged seizures to reduce their progression to SE. [34][35][36][37] Most episodes of pediatric SE start outside the hospital, 4,8 and delays to treatment administration are common 8 and associated with worse outcomes.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%